Catalan brinkmanship tool for political rivalry in Spain = Kataloński brinkmanship narzędziem rywalizacji politycznej w Hiszpanii - Górnicka, Weronika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this article is to analyze the independence activities undertaken by the Catalan government in the context of the brinkmanship strategy and the assumptions of game theory based on "the game of chicken". It allows us to put the issue of Catalan`s claims in a different context than to refer to political, historical or cultural grounds for self-determination.
Keywords: Catalonia; Spain; "the game of chicken"; brinkmanship; independence; Katalonia; Hiszpania; "dylemat kurczaków"; Niepodległość